2006
DOI: 10.1038/sj.bdj.4813466
|View full text |Cite
|
Sign up to set email alerts
|

A novel technique using preformed metal crowns for managing carious primary molars in general practice — A retrospective analysis

Abstract: BackgroundThere is a high level of untreated dental decay in primary teeth in Scotland. Despite evidence for the efficacy of preformed metal crowns (PMCs) for the restoration of primary molars, few are placed in general practice, possibly due to the interventive nature of the clinical procedure. There is, however, a novel way of placing PMCs involving no local anaesthesia, no caries removal and no preparation of the tooth: the Hall technique. Aim To investigate the survival of carious primary teeth treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 18 publications
(22 reference statements)
8
102
0
9
Order By: Relevance
“…The technique is considerably less demanding than the conventional approach and thus offers an invaluable restorative option for more junior dental students. 16,17 Another interesting finding arising from this study was that in the two centres with a signifi cant outreach component (Manchester and Sheffi eld), students were more likely to have carried out primary molar pulp therapy and extractions in outreach clinics than during hospital sessions. This may be explained by the difference in case-mix presenting to primary care and tertiary services.…”
Section: Inter-school Comparisonsmentioning
confidence: 83%
“…The technique is considerably less demanding than the conventional approach and thus offers an invaluable restorative option for more junior dental students. 16,17 Another interesting finding arising from this study was that in the two centres with a signifi cant outreach component (Manchester and Sheffi eld), students were more likely to have carried out primary molar pulp therapy and extractions in outreach clinics than during hospital sessions. This may be explained by the difference in case-mix presenting to primary care and tertiary services.…”
Section: Inter-school Comparisonsmentioning
confidence: 83%
“…The Hall technique uses SSC to seal over carious lesions on primary molars using glass ionomer cement with no caries removal, no crown preparation, and no local anesthesia. [7] In a randomized, controlled clinical trial, SSC provided using the Hall technique have shown to outperform standard class II restorations provided by general dentists. [8] In addition to comparative restoration success, the Hall technique was preferred over traditional restorative techniques by the child, caregiver, and dentist.…”
Section: Introductionmentioning
confidence: 99%
“…They extend from stepwise caries removal to nonrestorative caries treatment (NRCT), where no caries is removed but the cavity is opened to allow the lesion to be brushed by parent and child; the biofilm is altered through continual disruption/cleaning (Gruythuysen et al, 2011;Kidd, 2012). Additionally, sealing techniques include those with no caries removal, such as the Hall technique (HT; Innes et al, 2006Innes et al, , 2011, partial (Lula et al, 2009) stepwise caries removal (Ricketts et al, 2013), and fissure sealing lesions (Griffin et al, 2008). Although the evidence base supporting biological treatment approaches is growing, the limited comparative evidence for one approach over another leaves clinicians with uncertainty around their efficacy and, therefore, difficulties when planning treatment for children.…”
mentioning
confidence: 99%